A physical activity questionnaire: reproducibility and validity (2007)
This study evaluates the Quantification de L’Activite Physique en Altitude chez les Enfants (QAPACE) supervised self-administered questionnaire reproducibility and validity on the estimation of the mean daily energy expenditure (DEE) on Bogotá’s schoolchildren. The comprehension was assessed on 324 students, whereas the reproducibility was studied on a different random sample of 162 who were exposed twice to it. Reproducibility was assessed using both the Bland-Altman plot and the intra-class correlation coefficient (ICC). The validity was studied in a sample of 18 girls and 18 boys randomly selected, which completed the test - re-test study. The DEE derived from the questionnaire was compared with the laboratory measurement results of the peak oxygen uptake (Peak VO2) from ergo-spirometry and Leger Test. The reproducibility ICC was 0.96 (95% C.I. 0.95-0.97); by age categories 8-10, 0.94 (0.89-0. 97); 11-13, 0.98 (0.96- 0.99); 14-16, 0.95 (0.91-0.98). The ICC between mean TEE as estimated by the questionnaire and the direct and indirect Peak VO2 was 0.76 (0.66) (p<0.01); by age categories, 8-10, 11-13, and 14-16 were 0.89 (0.87), 0.76 (0.78) and 0.88 (0.80) respectively. The QAPACE questionnaire is reproducible and valid for estimating PA and showed a high correlation with the Peak VO2 uptake.